Accountability of Village Financial Management and Community Participation in The Development of Web-Based Village Government Information System in Sidoarjo East Java District - Diana Hertati; Nurhadi (Nusantara Science and Technology Proceedings)
One of the breakthroughs in improving information services for village governments is to use a web-based information system, which is useful to support the transparency of village financial management accountability systems so that village development supervision will be more clear and targeted, increasing community participation in village development and strengthening the quality of public services the village is better, then a web-based information system is needed. This study aims to find out: 1) Conceptual specification of web-based village government information system, for village government in Sidoarjo Regency, 2) Model of web-based village government information system implementation for village government in Sidoarjo Regency and 3) Guidelines for using village government information system web-based for village government in Sidoarjo Regency.The research location is the village administration in Sidoarjo regency. Data collection method is done by using interviews, focused groups and discussions. Data analysis was performed using qualitative analysis. This study found that there are dynamics in village financial management. Segoro Tambak Village has implemented village financial management in accordance with the principles of transparency and accountability. In contrast, Desa Tambak Oso has not yet realized village financial management in a transparent and accountable manner; and not yet in accordance with the regulations. Some of the obstacles faced by Tambak Oso village, including the ineffective guidance of village officials, lack of supervision, lack of personnel, and lack of understanding of the village apparatus with the applicable regulations.